A case study of using authentic assessment in project-based learning in excellent teachers' english classrooms - Muhammad Noor, Abdul Aziz (2019)
Authentic assessment is a variation of alternative assessment. It is a classroom assessment which comprises of teacher‟s observation, feedback as well as self and peer assessments. It can be used in student-centred teaching approaches namely project-based learning (PjBL). Although PjBL is recognised across the globe, not all teachers in the 21st century classrooms adapt this method with young learners. While authentic assessment advocates student-centred approach, this assessment method is still poorly implemented. To worsen the situation, primary school teachers do not have a guideline on how to use authentic assessment in their classroom. Excellent teachers who are model teachers use PjBL but lack knowledge on authentic assessment. This qualitative case study seeks to explore the process of using authentic assessment in assessing PjBL in the English classes of six excellent teachers from a Northern state in Peninsula Malaysia who were selected through purposive sampling. Data were gathered through semi-structured interviews, a series of classroom observations and document analysis. Atlas ti. Version 8 was used to aid the researcher in analysing and collapsing categories into emerging themes from the findings. Five themes that emerged were Student-centred learning; Teacher Quality; Variations in authentic assessment; Catering for learners‟ needs and Communicating assessment rubrics with learners. The implication of this research is for teachers to be able to use a set of guidelines from the best practices of the excellent teachers. The guidelines were developed from the findings to assist primary school teachers to embed authentic assessment in PjBL in their respective classrooms.